Peter Rabbit - Bazzi, Fayssal; Gluck, Will; Nalbandian, Zareh; Lieber, Rob, 1976-; Corden, James; Byrne, Rose; Gleeson, Domhnall, 1983-; Columbia Pictures; Sony Pictures Animation (Firm); Sony Pictures Home Entertainment (Firm) ([United States] : Columbia (USA), 2018)
Feature adaptation of Beatrix Potters classic tale of a rebellious rabbit trying to sneak into a farmers vegetable garden.
Title from container.
Special features: Peter Rabbit: Mischief in the making; Shake your cotton-tail dance along.
Originally released as a motion picture in 2018.
Wide screen (2.39:1).
Rating: PG; for some rude humor and action
CHV rating: G.
Keywords: Peter Rabbit -- (Fictitious character) -- Juvenile films; Rabbits -- Juvenile films; Gardens -- Juvenile films; Farmers -- Juvenile films; Comedy films; Animated films; Feature films; Childrens films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities